1999
DOI: 10.1126/science.285.5428.760
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Sortase, an Enzyme that Anchors Surface Proteins to the Cell Wall

Abstract: Surface proteins of Gram-positive bacteria are linked to the bacterial cell wall by a mechanism that involves cleavage of a conserved Leu-Pro-X-Thr-Gly (LPXTG) motif and that occurs during assembly of the peptidoglycan cell wall. A Staphylococcus aureus mutant defective in the anchoring of surface proteins was isolated and shown to carry a mutation in the srtA gene. Overexpression of srtA increased the rate of surface protein anchoring, and homologs of srtA were found in other pathogenic Gram-positive bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
829
1
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 950 publications
(845 citation statements)
references
References 18 publications
9
829
1
6
Order By: Relevance
“…Strains containing mutations in the genes encoding sortase A, alpha-hemolysin, protein A, and the global virulence regulators SarA and AgrA exhibit attenuated virulence in mouse models of pneumonia (12,18,47). Sortase A catalyzes the anchoring of proteins, including protein A, into the cell wall peptidoglycan (30). Gomez et al showed that protein A binds to TNFR1 to induce airway inflammatory responses during S. aureus infection (12).…”
mentioning
confidence: 99%
“…Strains containing mutations in the genes encoding sortase A, alpha-hemolysin, protein A, and the global virulence regulators SarA and AgrA exhibit attenuated virulence in mouse models of pneumonia (12,18,47). Sortase A catalyzes the anchoring of proteins, including protein A, into the cell wall peptidoglycan (30). Gomez et al showed that protein A binds to TNFR1 to induce airway inflammatory responses during S. aureus infection (12).…”
mentioning
confidence: 99%
“…5). To date, there are other examples of machinery that combine two proteins/peptides such as ubiquitin ligase found in the ubiquitin-proteasome complex 27 , sortase 28 , which participates in peptidoglycan biosynthesis, and intein, which is active in protein splicing 29 . However, PGM1 uses a completely distinct mechanism from these enzymes, and thus defines a new type of machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the predicted amino acid sequence of orf365 shares significant homology with a sortase identified from S. oureus. The sortase is involved in cleaving the conserved anchor consensus, LPXTG, between threonine and glycine as well as in anchoring the cleaved fragment to the peptidoglycan cell wall (Mazmanian et al, 1999). A mutation in or365 leaves monomeric FimA, which possesses the anchor domain, unassembled.…”
Section: Oto 1998) Andmentioning
confidence: 99%